Percepción cultural de los pobladores sobre el Programa Social Juntos en el Valle del Mantaro - Chanca Flores, Aparicio (2020)
Juntos is a conditional transfer program, part of the national strategy Crecer; it is aimed at improving the quality of life of the most needy Peruvians and promoting the development of human capital, providing better services of health, education and nutrition. This study had as objective to know the cultural perception the non-beneficiary inhabitants from Mantaro Valley have about the Juntos program. The research was of basic type and descriptive level. The analysis units considered were the non-beneficiary inhabitants, both male and female, from the four provinces of the Mantaro Valley: Concepción, Chupaca, Huancayo and Jauja. Using a probabilistic and cross-sectional sampling, it was determined a sample of 382 people over 15 years old, who were administered a Likert scale questionnaire. For the processing and analysis of data, descriptive statistics were used, obtaining as a result that the cultural perceptions non-beneficiary inhabitants have about the Juntos program are positive; most respondents perceive positive aspects in the execution of Juntos since this has been having an impact on the change of the beneficiaries’ attitudes and customs regarding nutrition, health and education activities.   DOI: https://doi.org/10.31876/sl.v4i1.49